Het gemeentelijk gasbedrijf, de cokesafdeling. Kopie van exemplaar op Gemeentelijke Archiefdienst Rotterdam (neg.nr.: G 22635) (1887)
Het gemeentelijk gasbedrijf, de cokesafdeling. Kopie van exemplaar op Gemeentelijke Archiefdienst Rotterdam (neg.nr.: G 22635).